Psychological distress as mediator in relationship between food insecurity and academic performance among undergraduate students in public university in Malaysia - Ahmad, Nor Syaza Sofiah (2022)
Students were expected to perform well in their studies, however it is not easy. A hectic life and struggle to meet basic needs put them at risk of food insecurity and psychological distress. The alarming concern on high prevalence of food insecurity and psychological distress is a threat to students’ success. Therefore, this study aimed to determine the mediating role of psychological distress in relationship between food insecurity and academic performance among undergraduate students in public university in Malaysia. By knowing the mechanism of these relationship, other researchers can help better understanding to plan intervention and improve students’ quality of life. In this cross-sectional study, a total of 663 undergraduate students in seven randomly selected faculties in Universiti Putra Malaysia were recruited. An online survey via Google form was conducted to obtain demographic and socioeconomic information, food security status, psychological distress and Cumulative Grade Point Average (CGPA). Chi-square test was used to determine the association between demographic and socioeconomics with food security status, Pearson correlation was used to determine the correlation between food security, psychological distress and academic performance meanwhile Binary Logistic Regression analysis were used to determine factors associated with food security status. PROCESS macro for SPSS was used for test the mediation. Among the participating students, 32.4% are male with majority were Malay (68.5%), single (96.2%), not working part-time (94.9%), living inside campus (82.7%) and financial aid recipient (91.4%). About 62.8% reported to have experienced food insecurity. The prevalence of stress (34.5%), anxiety (77.3%) and depression (40.1%) was reported among respondents. Majority of respondents (88.6%) had CGPA <3.75 while 11.4% had CGPA ≥3.75 for academic performance. There are associations between working parent, monthly household income, financial aid recipient, positive financial balance and perception on financial aid received (p<0.05) with food security status. Meanwhile, food security status was significantly associated with psychological distress (stress, anxiety and depression) and academic performance (p<0.05). Binary logistic regression revealed that students with unemployed father (AOR = 1.875, 95% CI: 1.22, 3.074), from low income group (AOR = 2.021, 95% CI: 1.257, 3.250), financial aid recipient (AOR = 2.811, 95% CI: 1.602, 4.932) and those who have extra money (AOR = 8.024, 95% CI: 2.556, 25.195) were associated with food insecurity. Mediation analysis revealed that anxiety and depression as mediating variables in the relationship between food security status and academic performance (p<0.05). The high prevalence of food insecurity in this study suggests that it is the main concern currently faced by students. Students with unemployed father, low monthly household income, and financial aid recipient were the main predictors for food insecurityamong students in this study.Results from mediation analysis showed that anxiety and depression mediated the relationship between food security status and academic performance. In other word, food insecurity increased anxiety and depression, in which this decreased the academic performance among university students. Overall, this study suggests that food insecurity has a negative impact on academic performance via anxiety and depression. Besides, these results demonstrate the importance of psychological health especially among those university students with food insecurity to improve their performance in academic.